Effect of citral partitioning on structural and mechanical properties of lipid membranes - Saraf, Deepashri; Porte, Sudha; Sengupta, Durba (European Physical Journal-Special Topics, 2024)
Delineating the interactions of cellular metabolites with lipid membranes and their effects on membrane physical and mechanical properties constitutes a key step for comprehensively understanding their biological function. The plant metabolite-citral is widely used in biotechnological and cosmeceutical processes, but significant gaps remain in our understanding of how it affects cellular membranes that it interacts with. In this study, we unravel the molecular mechanisms underlying the interactions of citral with compositionally distinct model membranes using atomistic molecular dynamics simulations. Specifically, we investigate two distinct membrane compositions: the neutral phosphatidylcholine-phosphatidylethanolamine (DOPC:DOPE) bilayer, representing mammalian cell membranes and the anionic phosphatidylcholine-phosphatidylglycerol (DOPC:DOPG) bilayer, mimicking bacterial cell membranes. Our simulations reveal that citral molecules readily partition into both membranes without distinct composition-dependent effects. Monomeric citral molecules localize mainly at the interface of the acyl chain region of the lipids, and a few translocation events are sampled in the simulations. Interestingly, we observe small differences in lipid fluidity although the citral molecules significantly influence the rigidity of lipid bilayers, and a higher bending modulus was observed in DOPC:DOPE lipid bilayers compared to DOPC:DOPG bilayers. Further, citral partitioning induces an increased tendency for lipid demixing in DOPC:DOPE membranes, as evidenced by the decreased values of the Shannon entropy. Our work is an important step to elucidate the molecular processes that underlie the differential impact of cell metabolites on compositionally distinct lipid membranes.